Karakteristik STEM dalam Perancang Konstruksi Mesin oleh Mahasiswa Pendidikan Teknik Mesin di Universitas Negeri Malang - Alfin Ageng Nandra Kurniawan; Dwi Agus Sudjimat; Didik Nurhadi (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2019)
STEM (Science, Technology, Engineering, and Mathematics) approach is an approach that answers the problems in engineering education. This research aimed to explore the students' STEM characteristic in Machine Construction Design, the obstacles that were experienced by the students when implementing STEM, and implementation pattern from STEM subjects. This research used the qualitative approach using a case study. The data was collected through the interview and documentation from the informant that consisted of supervisor lecturer of STEM subject and students who already took Machine construction Design subject. This research found that the students' STEM characteristics in Machine Construction Design subject consisted of: design task background that prioritizes problem-solving to understand the natural phenomenon in the context of machine construction design, CAD as a form of technology utilization to design the machine, machine element course content as a basis in material selection and computation of engine components, also mathematical engineering content to help understand the scope of physical engineering, CAD, and mechanical element. Meanwhile, the obstacles that often occurred were caused by external, internal, and technical of the course.